The Effects of School Integration: Evidence from a Randomized Desegregation Program - Peter Leopold S. Bergman (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the impact of a desegregation ruling on several medium-run outcomes. This ruling mandates that seven school districts, which serve higher-income, predominantly-white families, accept a group of minority elementary school students who apply to transfer from a nearby, predominantly-minority school district. Slots are allocated via lottery. The offer to transfer raises college enrollment by 10 percentage points. This is due to greater attendance at two-year colleges and particularly for male students. There is evidence male students are also more likely to vote. In contrast, transferring increases the likelihood of arrest. This is driven by increases in non-violent offenses.
Keywords: I20; I21; I24; I28; 330